Victorian Vampires: Cultural Anxieties in Nineteenth-Century Gothic - Murga Aroca, Aurora (Journal of Artistic Creation and Literary Research, 2025)
This essay attempts to reassess the figure of the vampire in Gothic literature by taking a close look to Bram Stoker’s Dracula (1897) and Sheridan Le Fanu’s Carmilla (1871). The paper establishes the connection between the two novels and points out some common concerns of their time by focusing on the social impact of the figure of the vampire, and the gender roles of the New Woman and the homosexual.